Peran Guru Agama dalam Meningkatkan Akhlak berbasis kearifan lokal: Studi Kasus di SMPN 1 Jepon Kabupaten Blora - Sofan, Sofan; Fitriana, Dyah Ayu; Jaya, Arim Irsyadulloh Albin (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2025)
The phenomenon of moral degradation among adolescents, including junior high school students, has become a serious challenge for Islamic education. This study aims to analyze the role of Islamic Education (PAI) teachers in improving students’ moral character through the integration of local wisdom values at SMP Negeri 1 Jepon, Blora Regency. This research employed a qualitative approach with a case study design. Data were collected through in-depth interviews with Islamic education teachers, observation of school religious activities, and analysis of documents related to moral habituation programs. The data were analyzed using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing, along with validity testing through source and technique triangulation. The findings reveal that Islamic education teachers play seven strategic roles in fostering students’ morality, namely as role models, motivators, spiritual guides, initiators of religious habituation, mediators of local cultural values, moral supervisors, and learning innovators. The integration of Islamic values with local wisdom such as Javanese proverbs and songs, the tradition of gotong royong (mutual cooperation), and regular worship practices has proven effective in cultivating students’ discipline, responsibility, solidarity, and politeness. This study concludes that the collaboration between Islamic values and local wisdom serves as an effective and contextually relevant approach to moral education in the modern era.ABSTRAKFenomena degradasi moral di kalangan remaja, termasuk siswa SMP, menjadi tantangan serius bagi dunia pendidikan Islam. Penelitian ini bertujuan menganalisis peran guru Pendidikan Agama Islam (PAI) dalam meningkatkan akhlak siswa melalui integrasi nilai-nilai kearifan lokal di SMP Negeri 1 Jepon Kabupaten Blora. Pendekatan yang digunakan adalah kualitatif dengan metode studi kasus. Data dikumpulkan melalui wawancara mendalam dengan guru PAI, observasi kegiatan keagamaan sekolah, dan analisis dokumen program pembiasaan. Analisis dilakukan dengan model interaktif Miles dan Huberman yang mencakup reduksi data, penyajian data, dan penarikan kesimpulan, disertai uji keabsahan melalui triangulasi sumber dan teknik. Hasil penelitian menunjukkan bahwa guru PAI memiliki tujuh peran strategis dalam pembinaan akhlak siswa, yaitu sebagai teladan, motivator, pembimbing rohani, penggerak pembiasaan ibadah, mediator nilai budaya lokal, pengawas moral, dan inovator pembelajaran. Integrasi nilai agama dengan kearifan lokal, seperti pepatah dan tembang Jawa, tradisi gotong royong, serta pembiasaan ibadah rutin, terbukti efektif menumbuhkan kedisiplinan, tanggung jawab, solidaritas, dan sopan santun siswa. Penelitian ini menegaskan bahwa kolaborasi antara nilai Islam dan kearifan lokal dapat menjadi pendekatan efektif dalam pendidikan akhlak kontekstual di era modern.